Fundamentals of mathematical statistics - Gupta, S. C.; Kapoor, V. K. (New Delhi: Sultan Chand & sons, 2002)
The book discusses the basics of statistics, discussing topics such as average, arithmetic mean, median, probability and types of distributions. It gives students an idea of statistical variation, and helps them understand how to study a population of data. The book provides a large quantity of problems for students to try solving, and provides some solved problems to demonstrate how the theory is used in practice. It covers a vast array of problems which are frequently asked in question papers, giving students an understanding of what to expect in the examination. The book is a must have for all GATE aspirants writing the mathematics paper.
Keywords: Probability; Statistics